ECONOMIC FOUNDATIONS OF THE MANAGEMENT OF ECONOMIC ACTIVITY IN THE FIELD OF HEALTH CARE - BILETSKA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The economic foundations of the management of economic activity in the field of health care are determined according to a comprehensive approach that covers the components, tasks and expected results of the adoption and implementation of management decisions. The components of the management of economic activity in the field of health care include financial management, management of intellectual and personnel support, management of material and technical support, investment management, management of innovative and technological support, analysis of economic activity, economic planning and forecasting of resource needs, risk management, efficiency monitoring and quality control of medical services. It has been established that the tasks of the management of economic activity in the field of health care are to strengthen the financial stability of the health care sector, increase the efficiency and motivation of the work of medical workers, optimize and increase the efficiency of the use of resources by enterprises of the industry, promote the introduction of innovative developments and technologies into the industry environment, economic evaluation of health care development programs, ensuring the availability of medical services, improving the quality of medical services. The expected results of the management of economic activity in the field of health care are proposed to consider the provision of rational distribution of limited financial and material resources, the reduction of economic barriers for the population to receive quality medical care, the modernization of medical infrastructure, the introduction of the latest technologies and modern treatment methods, the minimization of financial and organizational risks in the industry, implementation of social programs and improvement of the overall quality of medical care.